SISTEM DATA TERDISTRIBUSI UNTUK PENGELOLAAN DATA DONOR DARAH PADA UTD PMI KABUPATEN SUMBAWA MENGGUNAKAN METODE REPLICATION - Armelia Putrianjani; Yuliadi Yuliadi; Juniardi Akhir Putra; Farida Idifitriani (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The Indonesian Red Cross (PMI) is an institution or organization in charge of organizing, managing, and facilitating blood donor activities, from collection to distribution. Based on the results of interviews with officers of the Sumbawa Regency PMI blood transfusion unit, the blood donor data management process has previously used the system, but it has not been maximized, therefore researchers created a distributed data system with the replication method. The system is built using unified modeling language (UML), laravel as a framework with PHP programming language, and MySQL as a database. The research method used in this study is a qualitative method with observation, interview, and literature study stages, while the software development method uses Extreme Programming. This Extreme Programming method has advantages that allow the development team to create simple code so that it can be improved at any time. This research produces an integrated web-based system, with features of blood donor data, blood stocks, blood requests, and blood request reports.